2012
DOI: 10.1055/s-0031-1298157
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclo[4.4.0]decane Oxygenated Sesquiterpenes fromEryngium maritimumEssential Oil

Abstract: Investigation of the essential oil of the aerial parts of Eryngium maritimum L. from Corsica led to the isolation of one known sesquiterpene (1) and three new oxygenated sesquiterpenes with a muurolane or cadinane skeleton (2-4). Structure assignments of 4 βH -muurol-9-en-15-al (1), 4 βH -cadin-9-en-15-al (2), 4 βH -muurol-9-en-15-ol (3) and 4 βH -cadin-9-en-15-ol (4) were carried out by GC/MS (EI and CI) and comprehensive 1D and 2D NMR spectroscopy. Antibacterial activity of Eryngium maritimum L. oil and colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 6 publications
(8 reference statements)
1
14
1
Order By: Relevance
“…except for 4 β H‐cadin‐9‐en‐15‐al, 56 , and 4 β H‐cadin‐9‐en‐15‐ol, 58 , which were natural compounds identified for the first time in E . maritimum in our previous work . In addition, the Corsican oil sample was radically different to those reported by Aslan and Kartal in which spathulenol, 1,5‐epoxysalvial‐4(14)‐ene, α ‐amorphene and caryophellene oxide were identified as the main components.…”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…except for 4 β H‐cadin‐9‐en‐15‐al, 56 , and 4 β H‐cadin‐9‐en‐15‐ol, 58 , which were natural compounds identified for the first time in E . maritimum in our previous work . In addition, the Corsican oil sample was radically different to those reported by Aslan and Kartal in which spathulenol, 1,5‐epoxysalvial‐4(14)‐ene, α ‐amorphene and caryophellene oxide were identified as the main components.…”
Section: Resultscontrasting
confidence: 91%
“…Previous laboratory investigations of E . maritimum essential oil allowed the isolation of a known sesquiterpene (4 β H‐muurol‐9‐en‐15‐al) and three new oxygenated sesquiterpenes (4 β H‐cadin‐9‐en‐15‐al, 4 β H‐muurol‐9‐en‐15‐ol and 4 β H‐cadin‐9‐en‐15‐ol) which were efficient against Listeria monocytogenes and Echerichia coli …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It grows on coastal dunes of the Baltic Sea, the Mediterranean basin, and the Black Sea [5]. The phytochemical investigations of E. maritimum revealed the presence of secondary metabolites-polyhydroxylated oleanene triterpenoid saponins [6,7], phenolic acids, mostly rosmarinic and chlorogenic acids [8,9], flavonoids containing mainly kaempferol, astragalin, isoquercitrin, rutin, apigenin, and luteolin [8][9][10], coumarins [9], 20-hydroxyecdysone and polypodine B as the main phytoecdysteroids [11], betaines [12], and the essential oil [13][14][15][16][17][18][19]. Several studies concerning the essential oil composition of E. maritimum generally investigated aerial parts of the intact plant [13][14][15][16][17][18][19] and no other research dealt with biomass from in vitro cultures.…”
Section: Introductionmentioning
confidence: 99%
“…E. caeruleum essential oil (EEO) volatile compounds are responsible for many biological activities and are employed as antiseptic, appetizer, and laxative agents (Ghahraman, ). To the best of the authors' knowledge, several in vitro studies investigated the antimicrobial effects of the essential oils derived from the various species of Eryngium plant (e.g., E. palmatum , E. tricuspidatum L., E. caeruleum , E. maritimum , E. creticum , E. campestre , E. thorifolium , and E. duriaei ) by using microdilution and disk diffusion methods and determining the minimum bactericidal concentration (MBC; Abou‐Jawdah, Sobh, & Salameh, ; Çelik, Aydınlık, & Arslan, ; Darriet, Bendahou, Desjobert, Costa, & Muselli, ; Dehghanzadeh, Ketabchi, & Alizadeh, ; Marcetic et al, ; Meot‐Duros, Le Floch, & Magné, ; Merghache et al, ). However, no study was found to evaluate the antimicrobial effects of the Eryngium essential oils in the food models.…”
Section: Introductionmentioning
confidence: 99%